En los márgenes del canon y al borde de la sinrazón. Georg Büchner y el mundo al revés de Leonce und Lena - García Adanez, Isabel (Revista de Filología Alemana, 2010)
Almost a century had to pass before Büchner's works began to be appreciated or even known. And even though he is now unquestioningly included in the History of German and World Literature as one of the great authors of the 19th century, he cannot be completely integrated into any of the categories in which the different periods and tendencies are typically divided (as also happens with Kleist, Hölderlin, Jean Paul or Heine). So Büchner tends to be classified as "unclassifiable". He is now considered a canonical author, but he remains an outsider within this canon. Furthermore, not only the themes but also the formal stylistic devices he chooses can be seen as "marginal" in the sense of "transgressive" or "extreme". His comedy Leonce und Lena (1836), which at first sight may seem just a light and merry play, shows, however, the same grotesque, tragic, radical and modern elements in form and content, which can be found in his other works.
Keywords: Vormärz; Commedia dell'Arte; Grotesque; Verfremdung; Fatalism